2016
DOI: 10.1155/2016/7186137
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Profiles in Long-Term Strenuous Exercise

Abstract: The open window theory indicates altered immunity 3 to 72 hours after exercise. The J-curve describes the risk of illness in response to exercise. The aim of this study was to examine the secretion of proinflammatory and anti-inflammatory cytokines before and after long-term strenuous exercise. Fourteen marathon and 16 half-marathon runners and 10 military cadets participating in a military ranger-training course were recruited to this study. Within-subject design was used measuring levels of plasma cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 32 publications
4
43
1
Order By: Relevance
“…Additionally, post-effort increases in IL-10 and TNF-α levels were only seen in the YYRL1 group. According to literature data, the changes in pro-and anti-inflammatory cytokine levels depend on the intensity and duration of physical effort [48][49][50]. The increase in IL-2 concentration observed in our study is in accordance with the increase in the Th1 cell subset distribution.…”
Section: Post-effort Cytokine Releasesupporting
confidence: 89%
“…Additionally, post-effort increases in IL-10 and TNF-α levels were only seen in the YYRL1 group. According to literature data, the changes in pro-and anti-inflammatory cytokine levels depend on the intensity and duration of physical effort [48][49][50]. The increase in IL-2 concentration observed in our study is in accordance with the increase in the Th1 cell subset distribution.…”
Section: Post-effort Cytokine Releasesupporting
confidence: 89%
“…These characteristics disappeared after the additional final exhaustion test, when the proliferation rate of spleen cells increased even more than in sedentary animals, producing similar IFN-γ and IL-6 amounts to the non-trained rats (TE and TE24 groups), but higher IL-10 secretion (TE group). Similarly, an increase in plasma IL-10 levels was reported in runners immediately after running a marathon (Nielsen et al, 2016). Spleen cells from intensively trained rats showed a similar proliferative ability under the B cell stimulus PWM but secreted higher amounts of IL-6 and lower amounts of IL-10 than sedentary animals.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have reported that physical activity can induce an acute phase response characterized by an increase in multiple circulating cytokines and chemokines, such as Interleukin-1 (IL-1), Interleukin-6 (IL-6), Tumor Necrosis Factor α (TNFα), Epidermal Growth Factor (EGF), and Monocyte Chemoattractant-1 (MCP-1) [2527]. However, other studies have shown no significant changes in cytokine levels after exercise [2831], thus confirming that a lack of clarity exists on this issue, probably due to the complexity of the adaptive mechanisms during physical activity. Herein, we assessed the antioxidant and inflammatory status both at rest and after an acute, moderately intense exercise in sedentary, normal weight and overweight/obese young men, to test whether different early adaptive responses after a similar energy demanding stimulus may occur in these individuals.…”
Section: Introductionmentioning
confidence: 99%